PENGARUH JENIS AMELIORAN TERHADAP EFEKTIVITAS DAN INFEKTIVITAS MIKROBA PADA TANAH GAMBUT DENGAN KEDELAI SEBAGAI TANAMAN INDIKATOR - Nurhayati Nurhayati (Jurnal Floratek, 2011)
The objectives of this research were to study effects of some ameliorants (calcify dolomite, sea mud, and some biofertilizers) to some variables of C-organic, C/N, soil nitrogen, soil available P, N and P absorption, the infection of Bradyrhizobium and mycorrhiza, and soybean growth. This research was arranged in Randomized Complete Block Design with thirteen treatments and two replicates.  Provision of some amelioran exerted significant effects on numbers of root nodules, degree of mycorrhiza infection, and plant height of 5 week after planting (WAP). The best amelioran was calcify dolomite on which had positive responses to the increase of numbers of root nodules, degree of mycorrhiza infection, and plant height of 5 WAP. The second best was combination of Bradyrhizobium +Mos+ peat soil isolate mycorrhiza, which significantly increased numbers of root nodules, degree of mycorrhiza infection, and plant height of 5 WAP. The poor and the poorest ameliorants were sea mud+calcify dolomite and sea mud without dolomite, respectively, which caused reduction of numbers of root nodules, degree of mycorrhiza infection, and plant height of 5 WAP.